TOXICOLOGICAL ASSESSMENT OF COPPER SULPHATE ON CHANNA ORIENTALIS AND HETEROPNEUSTES FOSSILIS: LC50 VALUES AND MORTALITY ANALYSIS - Prasad, Nayan K.; Shachi, Kumari; Sahani, Suresh Kumar (PT. Antis International Publisher, 2024)
The adverse effects of heavy metals, particularly copper sulphate, released from industrial effluents on aquatic life are well-documented. In this study, we determined the LC50 values of copper sulphate for two freshwater air-breathing fish species, Channa orientalis (Bloch) and Heteropneustes fossilis (Bloch). The LC50 values for Channa orientalis were determined to be 33 ppm at 24 hours, 32 ppm at 48 hours, 21 ppm at 72 hours, and 7.5 ppm at 96 hours. For Heteropneustes fossilis, the corresponding LC50 values were 15 ppm at 24 hours, 13 ppm at 48 hours, 9.5 ppm at 72 hours, and 5 ppm at 96 hours. We observed a significant increase in mucus secretion at higher concentrations of copper sulphate as compared to lower concentrations. The potential mechanisms of fish mortality under these conditions are also discussed in detail